Nutritional risk in hospitalised children: an assessment of two instruments. (29th September 2015) - Ling, R; Hedges, V; Sullivan, P
Abstract : Aims: A child's nutritional status often deteriorates over the course of a hospital admission. No universally accepted paediatric nutritional screening tool exists. This study aimed to evaluate validity and ease of use two new instruments, STAMP and STRONG, for the assessment of nutritional risk of paediatric inpatients. Methods: In a cross-sectional study two trained investigators applied STAMP and STRONG, respectively, to eligible inpatients. Demographic data, clinical information, dietetic input and measurements of weight and height were recorded. Statistical analysis used weight-for-height (height <120 cm) and body mass index (height >120 cm) as proxies for acute undernutrition and height-for-age for chronic undernutrition. Correlation of assessed risk and two factors predictive of nutritional risk: anthropometric nutritional status and presence of nutritional intervention were used to evaluate validity of the instruments. Results: 43 children (mean age 6 years and 4 months) were assessed by STAMP and STRONG. Using STAMP the population was classified as 44% high risk, 28% medium risk and 28% low risk. Using STRONG, 25% were high risk, 46% were medium risk and 29% low risk. For validity, STAMP scores correlated to weight-for-height (p<0.01) and height-for-age (p<0.01) but correlation was not significant for body mass index (p>0.05). STRONG correlated to all anthropometric measures (p<0.01). For STAMP and STRONG, 60% and 83%, respectively, of children ranked as high risk received nutritional intervention. Both tools identified all of the acutely malnourished (Z score less than −2 weight-for-height, or body-mass-index) and seven of eight chronically malnourished children (Z score less than −2 height-for-age). STAMP took 10–15 min to apply, and involved measuring children's weight and height, and STRONG took 5–10 min. Conclusion: In terms of validity; STAMP correlates less closely to anthropometric assessment of nutritional status and identifies considerably more children who receive no nutritional intervention as high risk than STRONG. This suggests STAMP over-diagnoses nutritional risk. In terms of ease of use STAMP involves measurement of each child's weight and height. Only 12.5% of inpatients had heights recorded. STAMP takes approximately 10 min longer than STRONG. Both for validity and ease of use STRONG was superior to STAMP.